The relationship between smoking status and depression prevalence among first and second year medical students - Marakoğlu, Kamile; Çivi, Selma; Şahsıvar, Şule; Özdemir, Saniye (Journal of Dependence, 2006)
Objective: The aim of this study was to investigate relationship between smoking attitudes and depression prevalence among first and second year students of Meram Medical Faculty, Selçuk University. Method: In this descriptive and cross-sectional study we administered a questionnaire and Beck Depression Inventory (BDI) that has 21 questions to students in order to determine socio-demographic, smoking and depression status at first and second year in medical school. The study was carried out between February and March in 2006. X2 test was used for statistical analysis. Results: We reached 81.9% of total students (331/404) during the study period. The mean age was 19.51±1.37. As looked at the distribution of gender, 56.2% of them were male (186) and 43.8% of them were female (145). Smoking prevalence was detected as 16.0% (53/331). BDI score was found over 10 in 43.8% (145/331). According to BDI scores, depression degree was mild in 24.8% (82/331), moderate in 12.1% (40/331) and severe in 6.9% (23/331) of students. The mean BDI score was 11.13±7.9 (median=9, min=0, max=38) in female students and 8.96±8.27 (median=7, min=0, max=48) in male students. Depression scores of smokers were higher than non-smokers (p>0.05). Depression scores and smoking prevalence of students who live with their families were lower than the ones who live at hostel or other places (p>0.05). The smoking prevalence of smoker students families was found as high significant (p<0.05). Conclusion: Although smoking prevalence among first and second year medical students was lower than general population, the BDI score was over 10 in 43.8% of students so that our students are at risk psychologically. In order to support our students, giving special counselling by the related institutions may be useful.